Trang chủ » Hỏi đáp » Môn Toán (a+b)^3+(a-b)^3-2a^3 (x+y)^2-(x-y)^2 9^8.2^8-(18^4-1).(18^4+1) 30/01/2024 (a+b)^3+(a-b)^3-2a^3 (x+y)^2-(x-y)^2 9^8.2^8-(18^4-1).(18^4+1)
1. (a+b)^3+(a-b)^3-2a^3 =a^3+3a^2b+3ab^2+b^3+a^3-3a^2b+3ab^2-b^3-2a^3 =(a^3+a^3-2a^3)+(3a^2b-3a^2b)+(3ab^2+3ab^2)+(b^3-b^3) =6ab^2 2. (x+y)^2-(x-y)^2 =(x+y-x+y)(x+y+x-y) =2y.2x =4xy 3. 9^8 .2^8-(18^4-1).(18^4+1) =(9.2)^8-[(18^4)^2-1^2] =18^8-(18^8-1) =18^8-18^8+1 =1 Trả lời
(a+b)^3 + (a-b)^3 – 2a^3 = a^3 + 3a^2b + 3ab^2 + b^3 + a^3 – 3a^2b + 3ab^2 – b^3 – 2a^3 = (a^3 + a^3 – 2a^3) + (3a^2b – 3a^2b) + (3ab^2 + 3ab^2) + (b^3 – b^3) = 0 + 0 + 6ab^2 + 0 = 6ab^2 (x+y)^2 – (x-y)^2 = (x+y-x+y)(x+y+x-y) = 2y . 2x = 4xy 9^8 . 2^8 – (18^4-1)(18^4+1) = (9 . 2)^8 – [(18^4)^2 – 1^2] = 18^8 – (18^8 – 1) = 18^8 – 18^8 +1 = 1 Trả lời
2 bình luận về “(a+b)^3+(a-b)^3-2a^3 (x+y)^2-(x-y)^2 9^8.2^8-(18^4-1).(18^4+1)”